2021
DOI: 10.1016/j.wasman.2020.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing present and future availability of critical high-tech minerals in waste cellphones: A case study of India

Abstract: Highlights The amount of waste smartphones and feature phones in India was estimated. The volumes of critical high-tech minerals in waste smartphones and feature phones in India was evaluated. The corresponding implications can enhance the efficient cellphone management in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…Mobile phones (or Cell phones) contain a number of critical metals including PGMs. Pd is used in mobile phones at the rate of 15 tonnes/billion mobile phones [72] or 0.009 to 0.015 g/unit [42]. Although Tan et al [73] reported that they did not detect Pd in their study.…”
Section: Electronics and Electricalmentioning
confidence: 81%
See 1 more Smart Citation
“…Mobile phones (or Cell phones) contain a number of critical metals including PGMs. Pd is used in mobile phones at the rate of 15 tonnes/billion mobile phones [72] or 0.009 to 0.015 g/unit [42]. Although Tan et al [73] reported that they did not detect Pd in their study.…”
Section: Electronics and Electricalmentioning
confidence: 81%
“…The ITU report that there is currently approximately one phone for every individual on the planet [74]. The biggest growth and markets for these types of phones is China, followed by India [42]. Clearly mobile phone numbers are growing rapidly along with the amount of Pd sequestered in this technology.…”
Section: Electronics and Electricalmentioning
confidence: 99%
“… He et al (2021) projected that from 2020 to 2035, 1.7 billion units of out-of-use feature phones and 1.64 billion units of out-of-use smartphones will be generated in India. Due to this, certain recommendations that the Indian government can implement have been provided.…”
Section: Review Content Resultsmentioning
confidence: 99%
“…In addition, the cooperation between the manufacturers of electronic devices and local waste management authorities should be increased. He et al (2021) projected that from 2020 to 2035, 1.7 billion units of out-of-use feature phones and 1.64 billion units of out-ofuse smartphones will be generated in India. Due to this, certain recommendations that the Indian government can implement have been provided.…”
Section: Cost Of Recyclingmentioning
confidence: 99%
“…comparación con el estudioAristizábal-Alzate et al, (2021) en Colombia se conoce instituciones de quienes aprovechan los residuos tecnológicos demostrando que el 15.5 % se recicla de formas adecuadas, a diferencia de los estudios de Venegas et al, (2020);He et al, (2021) concluyen que la gestión de residuos tecnológicos ayuda a reducir problemas ambientales aplicando programas de reducción y aprovechando hasta 27 mil toneladas al año a nivel mundial.…”
unclassified